Difference in Profiles of Oxidative Stress Marker (MDA) in STEMI and NSTEMI - Kaninta Nuga Sekunda; Ariosta Ariosta; Charles Limantoro; Andreas Arie Setiawan (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
ABSTRACT Introduction: Acute Myocardial Infarction (AMI) results in necrosis of the myocardium due to blockage in the coronary artery. AMI is classified into two categories, STEMI and NSTEMI. AMI is a multifactorial condition closely related to the increase in production of reactive oxygen species (ROS). As the end product of lipid peroxidase, Malondialdehyde (MDA) is often used as a biomarker for oxidative stress. Purpose: To prove the difference between profiles of oxidative stress marker (MDA) in STEMI and NSTEMI. Methods: An observational analytic study with a cross-sectional study approach done in Dr. Kariadi Central Public Hospital and Diponegoro National Hospital, Semarang, Central Java, between April and September 2020. Subjects were diagnosed by the presence of chest pains and an increase in CKMB and troponin levels. The study was conducted on 47 subjects consisting of 20 STEMI samples and 27 NSTEMI samples. Serum MDA was examined using the TBARS method. Data were analyzed by a computer program. Results: Mean serum MDA in STEMI and NSTEMI was 0,22 ± 0,12 μmol/L and 0,82 ± 0,92 μmol/L respectively. From the statistical analysis, results showed that the difference in serum MDA concentrations between STEMI and NSTEMI were significant (p = 0,007). Conclusion: Malondialdehyde concentration in NSTEMI was significantly higher than in STEMI. It is suggested that further research be done to know which type of MDA is more accurate, to understand the effect of lipid profile towards STEMI and NSTEMI, and to put patient’s medical history into consideration. Key Words: Acute Myocardial Infarction, Reactive Oxygen Species, Oxidative Stress, Malondialdehyde